PELAKSANAAN FUNGSI PENGAWASAN DPRD TERHADAP PEMERINTAH DAERAH DALAM RANGKA MEWUJUDKAN GOOD GOVERNANCE - Anwar, Khairil (Universitas Madura, 2017)
The function of supervision is the authority of the house of assembly (DPRD) especially when it must do supervision over the implementation of local regulation and other rules, the usage of APBD, the policy making and performance of local government in organizing local development, and the execution of international cooperation in locality. Being main stakeholder in local public service, DPRD is expected to stimulate the improvement of public service quality. In reality, the mechanism to implement the function and task of supervision of DPRD over the government regency is not systematic. One reason is that there is no legal base for technical guide of supervision system. The committees in DPRD of government regency have undergone the supervision over local government but their supervision is not focusing upon their performance on task field of the committe, the supervision by the committee is a merely routine, not touching the core of problem, and still away from giving concrete solusion. The implementation of task and function of supervision in DPRD of regency over the government (Local Leader), therefore, must be supported by strong legal base, adequate fund to facilitate task and function implementation, and reliable facility, structure and infrastructure, as well as the sufficient backup from the secretariat of DPRD.